Pengaruh Current Ratio dan Debt To Asset Ratio terhadap Return On Asset pada PT. Matahari Department Store, Tbk di Jakarta Periode 2011-2020 - Kartono Kartono (Prodi Manajemen STIE Hidayatullah Depok, 2021)
This study aims to determine the effect of the Current Ratio and Debt to Asset Ratio on Return on Assets at PT. Matahari Department Store Tbk in Jakarta. The method used is explanatory research. The analysis technique uses statistical analysis with regression, correlation, determination and hypothesis testing. The results of this study Current Ratio has a significant effect on Return on Assets of 51.7%, hypothesis testing is obtained t count > t table or (2,927 > 1,989). Debt to Asset Ratio has a significant effect on Return on Assets of 59.4%, hypothesis testing is obtained t count > t table or (-3,423 > 1.989). Current Ratio and Debt to Asset Ratio simultaneously have a significant effect on Return on Assets obtained by the regression equation Y = 1.762 + 0.024X1 + -0.154X2 and the determination value is 62.5%. 2,770).